PENGEMBANGAN MEDIA PEMBELAJARAN KODULAR BERBASIS LITERASI SAINS PADA PEMBELAJARAN IPA BAGI KELAS 4 SD - Hanum, Anisa; Sari, Prima Mutia (Academy of Education Journal, 2023)
This research aims to develop Kodular-based science literacy learning media and determine the feasibility and response of teachers and students towards the media. The research adopts the ADDIE research and development methodology, consisting of five stages: analysis, design, development, implementation, and evaluation. Data for the research were collected through questionnaires and observations. The research sample consisted of fourth-grade students from one of the Kramat Jati State Elementary Schools. Media validation was conducted by a media expert, who gave a score of 82.68%, indicating high feasibility. Material validation was carried out by a subject matter expert, who gave a score of 87.98%, indicating that the material was highly appropriate. The results of the teacher's response test showed 93.59%, categorized as excellent, and the student's response was 86.96%, categorized as excellent. It can be concluded that the Kodular learning media is suitable and effective for developing science literacy skills, particularly in the topic of plant parts in science.